Diagnostic Value of the Serum Anti-Toxocara IgG Titer for Ocular Toxocariasis in Patients with Uveitis at a Tertiary Hospital in Korea - Bae, Ki Woong (Korean J Ophthalmol, 2016)
PURPOSE: This study evaluated the prevalence of ocular toxocariasis (OT) in patients with uveitis of unknown etiology who visited a tertiary hospital in South Korea and assessed the success of serum anti-Toxocara immunoglobulin G (IgG) enzyme-linked immunosorbent assay (ELISA) as a diagnostic test for OT. METHODS: The records of consecutive patients with intraocular inflammation of unknown etiology were reviewed. All participants underwent clinical and laboratory investigations, including ELISA for serum anti-Toxocara IgG. OT was diagnosed based on typical clinical findings. Clinical characteristics, seropositivity, and IgG titers were compared between patients diagnosed with OT and non-OT uveitis. The seropositivity and the diagnostic value of anti-Toxocara IgG was investigated among patients with different types of uveitis. RESULTS: Of 238 patients with uveitis of unknown etiology, 71 (29.8%) were diagnosed with OT, and 80 (33.6%) had positive ELISA results for serum anti-Toxocara IgG. The sensitivity and specificity of the ELISA test were 91.5% (65 / 71) and 91.0% (152 / 167), respectively. The positive predictive value of the serum anti-Toxocara IgG assay was 81.3%. Among patients with anterior, intermediate, posterior, and panuveitis, the prevalence rates of OT were 8.3%, 47.1%, 44.8%, and 7.1%, respectively; the seropositivity percentages were 18.1%, 47.1%, 43.7%, and 17.9%; and the positive predictive values were 38.5%, 95.8%, 92.1%, and 40.0%. The serum anti-Toxocara IgG titer also significantly decreased following albendazole treatment. CONCLUSIONS: OT is a common cause of intraocular inflammation in the tertiary hospital setting. Considering that OT is more prevalent in intermediate and posterior uveitis, and that the positive predictive value of the anti-Toxocara IgG assay is high, a routine test for anti-Toxocara IgG might be necessary for Korean patients with intermediate and posterior uveitis.